Fluorescence engineering in metamaterial-assisted super-resolution localization microscope - Choi Kyu Ri; Li Shilong; Ozerov Igor; Bedu Frédéric; Park Dong Hee; Joo Bin Chan; Wu Jeong Weon; Nic Chormaic Síle; Lee Yeon Ui (Nanophotonics)
Single-molecule localization microscopies have gained much attention for their efficient realization of a sub-diffraction-limit imaging with the resolution down to the 10-nm range. In contrast to conventional localization microscopes, which rely on particular fluorescent probes in specific conditions, metamaterial-assisted super-resolution microscopies can be implemented with any fluorescent dye under general conditions. Here, we present a systematic study of fluorescence engineering in metamaterial assisted localization microscopy by using cyclic group metasurfaces coated with a fluorescent film. Tailored variations are clearly demonstrated in both the photoluminescence intensity and the photobleaching lifetime of fluorophores based on the spatially varied Purcell effect near the metasurfaces. The enhanced emissions and blinking dynamics of the fluorophores on these metasurfaces lead to an increased signal-to-noise ratio, and therefore give rise to a super-resolution localization image with 0.9-nm localization accuracy. Our results are not only beneficial for super-resolution localization imaging but also push the control of light–matter interactions beyond the diffraction limit.